A Rare Coexistence in an Infertile Woman: Ligneous Disease in Cervix and Conjunctiva - Murat Özekinci; Mehmet Sakıncı; Cem Yaşar Sanhal; Elif Pestereli; Münire Erman Akar; İnanç Mendilcioğlu (Gynecology Obstetrics & Reproductive Medicine, 2013)
Ligneous disease involving the female genital tract is a very rare entity. We present a case of a patient who admitted to our clinic with the complaints of dyspareunia, postcoital bleeding and infertility. On speculum examination a nulliparous cervix with white plaques and hemorrhagic lesions around ostium were seen. Multiple samples were taken from the cervical lesions and histopathologic diagnosis was ligneous cervicitis and low grade cervical intraepithelial lesion. According to the characteristics of the disease, a conjunctival examination and biopsy were performed. Similar microscopic features in cervix were also determined and reported as ligneous conjunctivitis. She used cyclosporine and oral contraceptives in the following six months but there was no improvement on either ocular or genital lesions.